In the shadow of the sun - Castellan, E. M. (Feiwel and Friends, 2020)
In 1661 France, seventeen-year-old Henriette of England must navigate her arranged marriage to Louis XIV's brother while keeping her magical abilities a careful secret from all at the Sun King's court. Includes historical note
Keywords: Louis / XIV / King of France / 1638-1715 / Juvenile fiction; Château de Versailles (Versailles, France) / Design and construction / Juvenile fiction; Courts and courtiers / Juvenile fiction; Kings and rulers / Juvenile fiction; Arranged marriage / Juvenile fiction; France / History / Louis XIV, 1643-1715 / Juvenile fiction; Gay men / Juvenile fiction; Magic / Fiction; Courts and courtiers / Fiction; Louis / XIV / King of France / 1638-1715 / Fiction; Kings, queens, rulers, etc / Fiction; Arranged marriage / Fiction; Love / Fiction; France / History / Louis XIV, 1643-1715 / Fiction; Cours et courtisans / Romans, nouvelles, etc. pour la jeunesse; Rois et souverains / Romans, nouvelles, etc. pour la jeunesse; Mariage arrangé / Romans, nouvelles, etc. pour la jeunesse; Homosexuels masculins / Romans, nouvelles, etc. pour la jeunesse; JUVENILE FICTION / General; Louis / XIV / King of France / 1638-1715; Château de Versailles (Versailles, France); Gay men; Arranged marriage; Courts and courtiers; Kings and rulers; France; 1643-1715; Young adult fiction; Juvenile works; Fantasy fiction; Fiction; Historical fiction; History; Romance fiction; Young adult works; Love stories; Jugendbuch